INFLUENŢA RĂZBOIULUI ISRAELIANO-PALESTINIAN (2023) ŞI A RUSIEI ÎN PERTURBAREA DRUMULUI MĂTĂSII. CÂTEVA CONSIDERAŢII - Tușa, Enache (Revista de Știinţe Politice şi Relaţii Internaţionale)
In the new international context of the conflicts that have broken out in Ukraine and the Gaza Strip, we can speak of a very sensitive economic environment in which analysts have described the threats of the disrupting global trade. This risk is made possible by the potential economic opportunities and supremacy of China, whose influence in the Middle East has grown considerably over the past 15 years. The reconfiguration of the American policy and the shift of the center of gravity of the United States from the Indo-Pacific area, due to the war generated by the Russian invasion, has left uncovered an extremely important area in the trade flows that ensure global trade. The article presents the main vulnerabilities that the two conflicts create in the global economy and how the disruption of trade flows would generate major crises globally.